Rancang Bangun Smart Oven untuk Penguatan Industri Kuliner di Kota Malang - Widiyanti; Riana Nurmalasari; Achmad Romadin (MASALIQ, 2026)
The technological utilization gap continues to limit the efficiency and consistency of baking processes in culinary micro, small, and medium enterprises (MSMEs). This community service program aims to design, implement, and evaluate a smart oven as an appropriate technology for a culinary MSME partner in Malang City, which was purposively selected because it still used a conventional oven. The program implementation included surveys, interviews, problem analysis, training, equipment development, handover, operational assistance, and monitoring. Data were obtained through observation, technical testing, interviews, and documentation and were subsequently analyzed descriptively and comparatively based on temperature stability, baking time, energy consumption, and product success rate. The implementation results showed that the smart oven was able to maintain temperature stability through automatic set-point and time controls, increase baking efficiency by 15–20%, reduce energy consumption by up to 12%, and achieve a product success rate of 98%. These findings indicate that the application of an automatic control system accompanied by operational assistance can improve production process standardization, reduce baking failures, and maintain consistent product quality. This program contributes to providing a replicable model for implementing appropriate technology to strengthen the productivity, efficiency, and competitiveness of local culinary MSMEs.